Learning to see and understand developing visual literacy. (Center for Humanities, 1973)
Explores works by Leonardo da Vinci, Goya, Lichtenstein, Bierstadt, Picasso, Wyeth, Kelly, Albers and Matisse to show how great artists have expressed their feeling in their works.